2017
DOI: 10.1017/s1041610216002295
|View full text |Cite
|
Sign up to set email alerts
|

The influence of caregivers’ burden on the quality of life for caregivers of older adults with chronic illness in Nigeria

Abstract: This study concluded that there is a high prevalence of caregivers' burden resulting in poor HQRoL. In addition, burden and age are predictors of the quality of life of caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…In their testimonies, the caregivers pointed out the need to be constantly present with their relatives, expressing their carelessness with themselves because of the constant care being provided to their dependent family member. A study carried out with 325 older adult caregivers aged 60 years or older showed that the majority had physical functional limitations, as well as fatigue and lack of energy, in addition to not performing physical activity, constituting an event that interfered in their quality of life (21) . It is understood that sedentarism and/or absence of activities compromises the physical condition of the caregivers, leading to increase their musculoskeletal pain.…”
Section: Discussionmentioning
confidence: 99%
“…In their testimonies, the caregivers pointed out the need to be constantly present with their relatives, expressing their carelessness with themselves because of the constant care being provided to their dependent family member. A study carried out with 325 older adult caregivers aged 60 years or older showed that the majority had physical functional limitations, as well as fatigue and lack of energy, in addition to not performing physical activity, constituting an event that interfered in their quality of life (21) . It is understood that sedentarism and/or absence of activities compromises the physical condition of the caregivers, leading to increase their musculoskeletal pain.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the sub-Saharan ( Dotchin et al, 2014 and Mugisha et al, 2013 ) as well Nigerian studies on caregiving have focused on specific illness conditions especially mental illness ( Adeosun, 2013 and Jack‐Ide, Uys, & Middleton, 2013 ) and ( Yusuf, Nuhu, & Akinbiyi, 2009 ) older adults with hip fracture ( Diameta et al, 2018 ), cancer ( Akpan-Idiok & Anarado, 2014 ), and patients with End-Stage Renal Disease ( Oyegbile & Brysiewicz, 2017 ). Similarly, Faronbi (2018) and Faronbi and Olaogun (2017) quantitatively examined the burden of caregiving for older adults chronic illness. Despite all these arrays of studies, little information exists that qualitatively examines caregivers’ burden among caregivers of older adults with chronic illness from most low-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to clinical care experiences in many homebound patients in developed countries like the United States. Studies in both developed and developing countries indicate significant caregiver burden when caring for older chronically ill adults [11,12]. In a recent study of caregivers of older adults in Nigeria, the prevalence of severe caregiver burden was about 59%, with resultant poor health-related quality of life [12].…”
Section: Psychosocial Care With Strong Family Supportmentioning
confidence: 99%
“…In addition, caregiver burden confers an increased mortality risk and poor caregiver health compared to non-caregivers [11,12]. Since the psychosocial and caregiver support are crucial to the care of these vulnerable older adults and likely correlates with patient outcomes, it is important that clinicians assess for the presence of caregiver burden or risk of abuse or neglect during house calls, while providing caregiver counseling and support.…”
Section: Psychosocial Care With Strong Family Supportmentioning
confidence: 99%